Prognostic Value of Serum Exosomal AHCY Expression in Hepatitis B-Induced Liver Cirrhosis - Tong, Ling; Yan, Cuilin; Wang, Minjie; Yang, Jiajia; Wang, Hongmei; Wang, Ying (Frontiers in Medicine, 2021)
Objective: We aimed to investigate serum exosomal adenosylhomocysteinase (AHCY) expression in hepatitis B-induced liver cirrhosis (HBV-LC) patients and to determine the prognostic value of serum exosomal AHCY. Methods: We collected serum samples from 100 patients with chronic hepatitis B (CHB) and from 114 HBV-LC patients to test serum exosomal AHCY expression using ELISA. Results: Compared with the CHB and Grade A and B HBV-LC groups, the level of exosomal AHCY expression was significantly higher in the HBV-LC group [376.62 (291.50–448.02) vs. 248.12 (189.28–324.63), P > 0.001] and the Grade C HBV-LC group [408.70 (365.63–465.76) vs. 279.76 (215.16–336.07), P > 0.001], respectively. Serum exosomal AHCY expression and MELD score had a significant positive correlation (r = 0.844, P < 0.001). Survival curve analysis showed that patients with low exosomal AHCY expression had significantly longer survival than patients with high exosomal AHCY expression (P = 0.0038). The receiver operating characteristics (ROC) curve showed that the area under the curve (AUC) value for the mortality prediction ability of serum exosomal AHCY in HBV-LC patients was 0.921, which was higher than the values for the MELD score (AUC 0.815) and Child-Pugh classification (AUC 0.832), with a sensitivity and specificity of 93.41 and 76.00%, respectively. Conclusions: The serum exosomal AHCY level is a novel potential prognostic biomarker in HBV-LC patients, which may be great significance for the prognosis of HBV-LC patients.